Institutionalised children's understanding of HIV/AIDS. - Mahlobo, Bongiwe (My University, 2009)
Limited research has been conducted on children’s understanding of HIV/AIDS despite its widespread practice in South Africa today. This study aimed to explore this area, specifically investigating institutionalised children’s understanding of HIV/AIDS Increased mortality rates have been seen as a result of the pandemic. In addition, children are seen as vulnerable to the impact of HIV/AIDS. While some children are directly affected by HIV/AIDS, having lost their parents to the epidemic, other children are infected with the virus. Taking this into account, it was deemed useful to explore how children have made sense of HIV/AIDS. The participants for the current study were between the ages of 8 and 14 years, and they were drawn from a children’s institution in a black community within South Africa. The participants engaged in story telling and drawing as means of communicating their understanding of HIV/AIDS. They participated in the following activities: Draw A Person (DAP), Kinetic Family Drawing (KFD), Draw a picture of a person infected with HIV/AIDS, Drawing a picture of HIV/AIDS, and completing Incomplete Sentences in relation to their understandings of HIV/AIDS. They also answered relevant questions in relation to all their drawings. Thematic content analysis was used to analyse data, together with methods adopted from a study conducted by Wiener and Figueroa (1998). It was found that children have a basic understanding of HIV/AIDS, based on information they obtained from their educators, guardians, peers, and the media. Prominent themes arising from the findings are as follows: the visibility of HIV infection, the impact of HIV on relationships, HIV changing lives, preoccupation with death and dying, confusion about HIV/AIDS, and HIV and Morality. Generally, respondents were found to have a negative perception of HIV/AIDS. It was also found that although respondents seem to have some understanding of HIV/AIDS regarding modes of transmission, and ways of preventing transmission, confusion about HIV/AIDS was dominant.
Keywords: Children; HIV/AIDS